2019
DOI: 10.1590/s1980-220x2018030403530
|View full text |Cite
|
Sign up to set email alerts
|

Associação dos fatores de estresse e sintomas depressivos com o desempenho acadêmico de estudantes de enfermagem

Abstract: RESUMO Objetivo: Verificar a associação dos fatores de estresse e da sintomatologia depressiva com o desempenho acadêmico de estudantes de enfermagem. Método: Pesquisa observacional, transversal, quantitativa, realizada em uma universidade pública em Manaus. Utilizou-se de dados sociodemográficos para a caracterização dos estudantes, do coeficiente de rendimento escolar e rendimento semestral individual, da Escala de Avaliação de Estresse em Estudantes de Enfermagem e da Escala de rastreamento de sintomatolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
22

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 21 publications
0
13
0
22
Order By: Relevance
“…Diverse mental disorders have been afflicting university students, who are considered a vulnerable population. Epidemiological studies show that their first symptoms manifest at the beginning of adult life, when students are in a transition period (1)(2) . Health courses, aimed at educating professionals to provide care, have the most psychologically unsound students (2) , which is particularly true of nursing (1,3) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Diverse mental disorders have been afflicting university students, who are considered a vulnerable population. Epidemiological studies show that their first symptoms manifest at the beginning of adult life, when students are in a transition period (1)(2) . Health courses, aimed at educating professionals to provide care, have the most psychologically unsound students (2) , which is particularly true of nursing (1,3) .…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies show that their first symptoms manifest at the beginning of adult life, when students are in a transition period (1)(2) . Health courses, aimed at educating professionals to provide care, have the most psychologically unsound students (2) , which is particularly true of nursing (1,3) . Individual, academic, and contextual variables are related to the process of resilience and illness in these individuals (1) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Students who had difficulty in studying at home may worry about their academic performance. A large number of studies have shown that adolescents' poor academic performance was closely associated with a high prevalence of depression [22][23][24]. Remote learning has been reported to have several disadvantages, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…First, this results from the fact that they are facing a new, totally unknown environment that is different from their secondary education environment, which forces behavioral changes in order to adapt to the new setting [4]. Second, the responsibility that comes with dealing with patients and their pathologies is extremely stressful [5].…”
Section: Introductionmentioning
confidence: 99%